Analisis Program Pencegahan dan Pengendalian Infeksi dalam Pelaksanaan Surveilans Hai’s di Rumah Sakit Bhayangkara TK II Sartika Asih Bandung - Fitri Faridath; Ericka Aulia Rosyidah; Nurul Dwi Aryani (Jurnal Health Sains, 2021)
Hospital is an institution engaged in health by optimizing health services in an effort to improve the degree of health for the community. This study focuses on the analysis of infection control and prevention programs in the implementation of HAI's surveillance, the aim is to see the main problems in hospital infections, namely referring to the hospital's ability to prevent or minimize the rate of increase in infection, The method used is descriptive qualitative research method, where research data are described in data collection through observation using phenomenological research methods. Data from observations are selected and then categorized from the most relevant data. After doing the research, the results obtained from this research are the PPI program regarding HAI's surveillance at Bhayangkara TK II Sartika Asih Hospital Bandung includes reporting of nosocomial infections such as Phlebitis, Decubitus, UTI (urinary tract infection), VAP (ventilator associated pneumonia) and IDO (operation area infection). And this hospital has reported HAI's surveillance incidents by the IPCN Committee.